حديث اعدد ستا بين يدي الساعة دراسة تحليلية Hadith of count six signs before the hereafter analytical study - Mohamed Fathy, Mohamed Abdelgelil; Asim, Al-Inazi; Mushrif, Al-Zahrani (2019)
Belief in the Hereafter signs is part of the Pillars of Belief in the Hereafter. Likewise, Belief in the Hereafter is a part of the Pillars of Faith. Similarly, in the Sunnah, as there are sound hadiths, there are weak hadiths. What makes the weak hadiths sound is the collection of Hadith’s phrases and chains of narration scattered among the books of Sunnah, and knowing the phrases of the Hadith which are in the Two Sahihs (Sound collection of Hadiths) or one of them. The research talks about some signs of the Hereafter mentioned in the Hadiths, verifying them according to their references and knowing the phrases which are not in the two Sahihs and then check whether they are sound or not. Among the aims of the research is to state the signs of the Hereafter and relate them to the reality we live. With people’s involvement in the overt and covert temptations, it is incumbent to be armed with knowledge. The research was conducted based on the inductive analytical methodology to induce all chains of narrators and phrases in the Hadith of Awf bin Malik, and to analyze them to find out which of Hadith of Awf bin Malik’s narration chains and phrases are sound or weak. The results have shown that belief in the signs of the Hereafter is part of the belief in the unseen without which no one’s faith is valid. In addition, it is obligatory to follow what is mentioned in Hadith either the abundantly narrated or the unique, and that the Hadith of Awf bin Malik is sound. Moreover, Malik (may Allah be pleased with him) has witnessed three signs of the Hereafter mentioned in his Hadith.